ANALISIS PENDAPATAN USAHATANI PADI SAWAH BERDASARKAN MUSIM PANEN DI KELURAHAN TARATARA SATU KECAMATAN TOMOHON BARAT KOTA TOMOHON - Fremar Refel Welang; Joachim N.K. Dumais; Martha M. Sendow (AGRI-SOSIOEKONOMI, 2016)
This study aims to determine the magnitude of paddy rice farm income and determine how the feasibility of paddy rice farming by the harvest season in Taratara One Village, West Tomohon Sub-district, Tomohon City. The research was carried on three months, from Februari to April 2016, which is located in Taratara One Village. The Samples of farmers is using simple random sampling method (simple random). Data analysis in this research using descriptive analysis with the help of the table, and to determine the amount of income using the formula: I = TR – TC. And the feasibility of farming using analysis of return ratio by the formula: a = R : C. Based on the analysis, the average farm income of paddy rice farmer managed respondents in Taratara One Village by harvest season for the first harvest season 1 (one) Rp. 22,664,971.19 per hectare and the second harvest 2 (two) Rp. 18,541,100.85 per hectare. Rated Ratio/Cost for the first harvest season one (1) by 3.46 and harvest 2 (two) of 2.83. Based decision rule if the value of R/C is more than one, it means paddy rice farming can provide benefits and well work the effort.